Impact of Lime and Cement on Various Lateritic Soil Samplings as Construction Material (Journal of Science and Technology, 2022)
This study was performed so as to evaluate engineering properties and strength of lateritic soils stabilized with hydrated lime and Portland cement as construction materials. Soil samplings P1, P2, P3, P4, and P5 was collected from Dualization of Sheda - Abaji, Abuja, F.C.T, Nigeria and stabilized with 0, 3, 6, 9, and 12% of hydrated lime and Portland cement.  Many laboratory tests were performed on the soil sampling such as Consistency (Atterberg limit), California Bearing Ratio (C.B.R), water absorption, compaction test and particle size distribution. The research revealed that beneficial impacts were obtained thru the addition of hydrated lime and Portland cement in order to increase the strength of poor or weak soils. C.B.R values are 9.98, 9.88%, 8.36%, 7.89% and 7.27% for samplings P1, P2, P3, P4 and P5 respectively at 0% additive content and at 12% additives, the samplings gave C.B.R values of 59%, 55%, 53%, 51.0% and 50.00% by using cement. All the five samplings have highest C.B.R values of 48.0% with hydrated lime as additives. Introduction of additives improved the soil samplings from a very poor subbase and base materials to an excellent base material with C.B.R values over 40%. Thus, improvement of laterite soil samplings from the studied locality can be perform successfully by using Lime judging from the outcome of the different tests on the various soil admixtures.